(untitled) (Fiep Bulletin - online, 2014)
The adolescence is a period of physical and emotional change in subjects where the physical and social changes are visible. Some of them are expected attitudes triggering of diseases that directly affect the way they perceive their bodies. The body image is constructed multidirecionalmente from influences that the individual receives the social environment, "we are under pressure in many circumstances to achieve in our body, the body ideal of our culture" (TAVARES, 2003, p. 17). Basing itself this assumption, this research aims to examine the body image associated with eating disorders and see how the physical education can be used as a resource in their fight and prevention in adolescents and pre-adolescents. The sample was 79 students. The instruments used to collect data were: questionnaire, silhuetas of scale, body image, Tiggeman & Wilson Barret (1998), digital scales and estadiômetro. It was done the calculation of BMI and the results were analyzed together with tests on body image in order to verify the possible link between the actual values and ideals in the design of the students. The sample studied as a whole has not produced significant differences. However, some groups such as the age of 14 years of female overweight and presented it along with the Body Image represented was 7. Even with these differences, there was a prevalence of silhuetas 5.5 and 6.0 which may be understood as a small distortion. While the silhuetas not distanciassem both the real picture which makes them not so susceptible to eating disorders, the professor of physical education to provide these students on the concepts and issues stemming from overweight that may affect the health, but above all, show an ideal body is what each feels well and not one that society imposes.